دراسة و قياس فاعلية الصورة الذهنية بالتعرف على المكان الحضري في المدن "مدينة صنعاء حالة دراسية" - شمس الدين، منيف; المذحجي، محمد سلام (University of Science and Technology, Yemen, 2015)
Identifying spacesin a city based on the mental image is one of the current serious problems that people face because of the further deterioration and visual pollution, and the loss of the optical and cognitive properties of the physical elements and components in the urban empty spacesof cities. Many previous studies particularly the local have neglected to investigate the mental image effectiveness to identify urban spacesin cities. Therefore, an urgent need for a study which mainly discusses the mental image and its positive and negative effects on receivers when they want to identify urban empty spacesof cities. Therefore, the study aims to investigate the mental image effectiveness in letting users be able to identify urban empty spacesof cities. To reach this goal, a methodology based on the integration of two main axes. The first focuses on a theoretical study for the mental image to identify locations and urban empty spacesin Yemen, and to determine the study space. While, the second focuses on a practical study for the urban empty spaces(the study area) of Sanaa city by conducting a questionnaire. Then, results have been found. They identify how the mental image of urban components of users is so clear and how this clarity affects their ability to identify urban empty spacesin the study area. After that, the results of the practical study are discussed and the conclusions are found. Finally, the study ends with some recommendations that helps in addressing and solving urban problems in order to have a clear mental image to identify urban empty spacesof Sanaa city.